The communicative function of destination memory. (22nd January 2018) - El Haj, Mohamad; Miller, Ralph
Abstract: Mahr & Csibra's (M&C's) proposal that episodic memory has a role in communicative interaction is innovative. However, the model would be strengthened by the inclusion of the construct of destination memory. Destination memory refers to the ability to remember to whom one has sent information. Research has demonstrated that this ability is essential for communicative efficacy and daily interactions with others.